Simulation of intersection of complicated information signals in air traffic control systems - Коба, Е. В. (Proceedings of National Aviation University (archive), 2000)
Considered is the problem of complicated system simulation with customers incoming flows. Developed is an algorithm accelerated of finding probability of the superposition of complicated customers. Derived are the top and bottom estimates of damage-factor which are connected with complical customers superposition. Noticed is connection with simulation problem of air traffic control system